SOSIALISASI PENTINGNYA MENJAGA TEKANAN DARAH PADA LANSIA DI RT.16/04 KELURAHAN RAWABUAYA: SOCIALIZATION OF THE IMPORTANCE OF MAINTAINING BLOOD PRESSURE IN THE ELDERLY IN RT.16/04 KELURAHAN RAWABUAYA - Emil Emil (Jurnal Pengabdian Masyarakat Kesosi, 2020)
The elderly are a group of people who have different characteristics from other age groups, because the elderly are generally characterized by decreased physical, social, and psychological functions. The deterioration of organ structure and function also occurs in the cardiovascular system, one of which is that the walls of the arteries have thickened and stiffened due to arteriosclerosis so that blood is forced to pass through narrower vessels than usual and causes blood pressure to rise. When you reach the age of 60 years, an elderly person's blood pressure will tend to start to increase. However, blood pressure will tend to decrease when the elderly reach the age of 80 years or more. High or low blood pressure in the elderly may not cause symptoms. Through this community service activity, it is hoped that the elderly will gain an understanding of the importance of always controlling and checking blood pressure conditions. The purpose of this socialization is primarily so that the elderly can avoid complications of health problems that can occur due to the influence of uncontrolled blood pressure. In addition, life expectancy and survival in old age can be of higher quality. The results of the socialization activities describe success, as can be seen from the increasing level of knowledge of the respondents as measured through the pretest and posttest stages